Determinants of innovation and performance in a disrupted environment - (:unkn) unknown (My University, 2023)
The constraints imposed by the Covid-19 pandemic have pushed organizations to find innovative solutions to perform in a disrupted environment. In the African context, however, some public and private institutions have been unable to rise to the challenge. Our case is an exception. The resource-based approach enables us to understand how a private higher education institution that was one of the few to migrate rapidly to distance learning was able to do so. We use the grounded theory method to analyze our data with Nvivo software. We note the institution's prior commitment to a digital strategy before the arrival of the pandemic, which enabled it to rapidly mobilize its logistical and human resources in IT, and to build the professional and resilience capacities of its staff in order to innovate by introducing a new form of teaching to perform well in a disrupted environment.
Keywords: African Research